Effects of IGF-1 on IK and IK1 Channels via PI3K/Akt Signaling in Neonatal Cardiac Myocytes - Richard M. Millis; Zikiar V. Alvin; Aiqiu Zhao; Georges E. Haddad (International Journal of Cell Biology)
Previous studies suggest that sarcolemmal potassium currents play important roles in cardiac hypertrophy. IGF-1 contributes to cardiac hypertrophy via activation of PI3K/Akt signaling. However, the relationships between IGF-1, PI3K/Akt signaling and sarcolemmal potassium currents remain unknown. Therefore, we tested the hypothesis that IGF-1 and PI3K/Akt signaling, independently, decrease sarcolemmal potassium currents in cardiac myocytes of neonatal rats. We compared the delayed outward rectifier (IK) and the inward rectifier (IK) current densities resulting from IGF-1 treatments to those resulting from simulation of PI3K/Akt signaling using adenoviral (Ad) BD110 and wild-type Akt and to those resulting from inhibition of PI3K signaling by LY294002. Ad.BD110 and Ad.Akt decreased IK and these decrements were attenuated by LY 294002. The IGF-1 treatments decreased both IK and IK1 but only the IK decrement was attenuated by LY294002. These findings demonstrate that IGF-1 may contribute to cardiac hypertrophy by PI3K/Akt signal transduction mechanisms in neonatal rat cardiomyocytes. Failure of LY294002 to effectively antagonize IGF-1 induced decrements in IK1 suggests that a signal pathway adjunct to PI3K/Akt contributes to IGF-1 protection against arrhythmogenesis in these myocytes. Our findings imply that sarcolemmal outward and inward rectifier potassium channels are substrates for IGF-1/PI3K/Akt signal transduction molecules.